The Position of Contract Marriage Law (Nikah Mut`Ah) in Indonesia: A Comparative Study - Teuku Yudi Afrizal (Journal Research of Social Science, Economics, and Management, 2022)
In the aspect of Islamic law, mut'ah marriage was allowed by Rasulullah SAW only during the war. But the permission has been abolished or the law of mut'ah marriage is forbidden and sinful for those who do it. In the aspect of national law, contract marriage is considered a legal defect because it is contrary to Article 2 paragraph (1) of Law Number 1 of 1974 on Marriage, Article 1337 and Article 1332 of the Civil Law, the principle of marriage and the purpose of marriage. Based on these provisions, a legal marriage is conducted in accordance with the teachings of religion and beliefs and is not contrary to the values ??of morality. Marriages that are registered or registered in accordance with applicable laws and regulations will receive protection from the State. The practice of contract marriage actually positions the position of women is very weak in the eyes of the law because the marriage is considered never happened, so the wife is not considered a legitimate wife, the wife is not entitled to alimony and inheritance from the husband if he dies and the wife is not entitled to gono gini property if it occurs. separation, because legally the marriage, the contractual marriage is considered to have never occurred.